Interpreting Love Narratives in East Asian Literature and Film - Wallace, John (Open textbook library., 2019)
This book explores the role of traditional East Asian worldviews, ethical values, and common practices in the shaping of East Asian narratives in literature and film. It offers a specific method for this analysis. The interpretive goal is to arrive at interpretations that more accurately engage cultural information so that narratives are understood more closely in terms of their native cultural rather than that of the reader/interpreter. Current neuroscience related to processes of perception and the attribution of meaning form the basis for the theory of interpretation offered in the first half of the volume.